2021
DOI: 10.1111/jocs.15335
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes in CABG patients with atrial fibrillation associated with surgical left atrial appendage exclusion

Abstract: Background We sought to determine the impact of left atrial appendage clip exclusion (LAACE) on coronary artery bypass grafting (CABG) outcomes among patients with pre‐existing atrial fibrillation (AF). Methods From October 1, 2015 to October 1, 2017, 4210 Medicare beneficiaries with pre‐existing AF underwent isolated CABG (i.e., without ablation) with (n = 931) or without (n = 3279) LAACE. Inverse probability of treatment weighting was used to evaluate the effect of concomitant LAACE on short‐ and long‐term o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…28 An observational, retrospective study of 4210 patients with AF undergoing CABG surgery found a 26% lower thromboembolic risk for patients with concomitant LAA closure over 1year mean follow-up, but not on isolated ischemic stroke risk. 30 A large, retrospective cohort study of patients with AF older than 65 years reported a 33% lower thromboembolic risk (sHR. 0.67 [0.79;0.97], P = 0.001) among mixed cardiac surgeries with concomitant LAA.…”
Section: Systemic Thromboembolisms After Laa Closurementioning
confidence: 99%
“…28 An observational, retrospective study of 4210 patients with AF undergoing CABG surgery found a 26% lower thromboembolic risk for patients with concomitant LAA closure over 1year mean follow-up, but not on isolated ischemic stroke risk. 30 A large, retrospective cohort study of patients with AF older than 65 years reported a 33% lower thromboembolic risk (sHR. 0.67 [0.79;0.97], P = 0.001) among mixed cardiac surgeries with concomitant LAA.…”
Section: Systemic Thromboembolisms After Laa Closurementioning
confidence: 99%
“…This prospective randomized multicenter trial finds support from a registry analysis from the Cleveland clinic that even shows an association between left atrial appendage occlusion and reduced CABG mortality. 23 Although clinically relevant strokes are rare, other, diffuse and cardiopulmonary bypass-associated neurological complications are often cause of discussion and fear. An important retrospective cohort study was published in 2021 assessing changes in the rate of memory decline after CABG or PCI.…”
Section: Surgical Treatment Of Coronary Artery Diseasementioning
confidence: 99%
“…This prospective randomized multicenter trial finds support from a registry analysis from the Cleveland clinic that even shows an association between left atrial appendage occlusion and reduced CABG mortality. 23…”
Section: Surgical Treatment Of Coronary Artery Diseasementioning
confidence: 99%
“…Currently, the Society of Thoracic Surgeons gives a Class IIa recommendation for closure of LAA with concomitant AF surgery, but this was before the publication of the landmark LAAOS III Trial. 9 Several publications have shown safety and improved outcomes with LAA closure, 10,11 including a recent randomized clinical trial. 9 There are several options for the surgical treatment of standalone AF.…”
mentioning
confidence: 99%